2013
DOI: 10.3892/or.2013.2910
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NEK2 is associated with drug resistance in ovarian cancer

Abstract: Abstract. NEK2 [NIMA (never in mitosis gene A)-related expressed kinase 2] is associated with various biological behaviors in the development of cancer, while research concerning its association with drug resistance is limited. The association of NEK2 with drug resistance in ovarian cancer has not yet been reported. In the present study, on the basis of microarray results from Oncomine and the GEO Profiles online database, we revealed that NEK2 mRNA expression in ovarian cancer tissues is upregulated. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 82 publications
1
62
0
Order By: Relevance
“…Using the comprehensive bioinformatics analyses, Yin et al (10) performed an integrated analysis of tumor suppressor genes with drug resistance in ovarian cancer, and two genes CCL21 and SPARCL1 associated with drug resistance were identified (85). Using similar bioinformatics analysis, upregulation of NEK2 was identified to be associated with drug resistance in ovarian cancer (86), and upregulation of E2F3 was identified to be associated with poor prognosis in HCC (87). The association of HNF1B with drug resistance in ovarian and other cancers has yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Using the comprehensive bioinformatics analyses, Yin et al (10) performed an integrated analysis of tumor suppressor genes with drug resistance in ovarian cancer, and two genes CCL21 and SPARCL1 associated with drug resistance were identified (85). Using similar bioinformatics analysis, upregulation of NEK2 was identified to be associated with drug resistance in ovarian cancer (86), and upregulation of E2F3 was identified to be associated with poor prognosis in HCC (87). The association of HNF1B with drug resistance in ovarian and other cancers has yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a comprehensive bioinformatics approach, including microarrays, motif analysis, protein/gene interaction, proteinchemical interaction, biological process annotation, pathway enrichment and mRNA-microRNA interactions, has been used to identify the association of dysregulated SPARCL1 and chemokine (C-C motif) ligand 21 (CCL21) (41), NIMArelated kinase 11 (NEK11) (95) and NIMA-related kinase 2 (NEK2) (96), and ribonuclease T2 (RNASET2) and gametogenetin binding protein 2 (GGNBP2) (97) with drug resistance in Table II. Top 10 microRNAs targeting TRPC1, as predicted by microRNA-mRNA interactions and their drug-resistance-related functions in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover in ovarian cancer, Nek2 mRNA expression is upregulated, especially in drug-resistant cells. The bioinformatic analysis revealed that Nek2 may directly or indirectly interact with a number of genes, proteins, microRNAs associated with drug resistance in ovarian and other types of cancer (28). Aberrant Nek2 expression has also been found in other cancers, such as non-small cell lung cancer and malignant peripheral nerve sheath tumor (29,30).…”
Section: Introductionmentioning
confidence: 99%